Designing of Machine to Make Sectional Flight Screw - Wahyudi, Retno; Sembiring, Alexander (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
An Auger resembles a large Screw, but its blades are designed to lift and move material, rather than fasten it like a Screw. The primary function of an Auger is to bore holes by rotating and using its blades to cut and extract material, thus clearing the hole. Manual leaf processing remains a common practice in many areas, which is time-consuming and labor-intensive, often resulting in inconsistent product quality. This process is inefficient and incurs high operational costs, reducing profits for farmers and small industries. This research aims to design and develop a leaf-making machine with a sectional Flight Screw type. The methodology includes literature review, prototype design and development, performance testing, and data analysis. The machine has dimensions of 63 x 21.5 x 57.5 cm, using materials such as 4x4 cm angle iron, 5 mm thick IWF iron, and 15 mm thick plate iron. The semi-mechanical Screw leaf-making machine has a maximum pitch length of 165 mm, a maximum Screw diameter of 360 mm, a maximum thickness of 10 mm, and a maximum torque of 3.5 kg.m, producing high uniformity among the Screw leaves made by the semi-mechanical Auger machine. Auger menyerupai sekrup besar, namun bilahnya dirancang untuk mengangkat dan memindahkan material, bukan mengencangkan. Fungsi utama Auger adalah mengebor lubang dengan memutar dan menarik material keluar. Pengolahan daun secara manual masih umum di banyak daerah, memakan waktu dan tenaga serta menghasilkan produk berkualitas tidak konsisten. Proses ini tidak efisien dan memerlukan biaya operasional tinggi, mengurangi keuntungan petani dan industri kecil. Penelitian ini bertujuan merancang dan mengembangkan mesin pembuat daun tipe Screw sectional Flight. Metodologi mencakup studi literatur, desain dan pengembangan prototipe, pengujian kinerja, serta analisis data. Mesin memiliki dimensi 63 x 21,5 x 57,5 cm, dengan bahan besi siku 4x4 cm, besi iwf tebal 5 mm, dan besi plat tebal 15 mm. Mesin semi mekanis ini memiliki kapasitas maksimal panjang pitch 165 mm, diameter daun Screw 360 mm, tebal 10 mm, torsi 3,5 kg.m, dan menghasilkan keseragaman tinggi.